2017
DOI: 10.1016/j.phro.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Surface doses of flattening filter free beams with volumetric modulated arc therapy dose delivery for breast cancer

Abstract: Background and purpose: Flattening filter free (FFF) beams enable high-dose rate irradiations and have the potential to speed up breast cancer radiotherapy (RT) treatments. In this work the surface doses of FFF beams were studied with various treatment plans for breast cancer RT. The near surface dose distributions were compared to the ones delivered with conventional flattening filter (FF) beams and to the calculated dose distributions. Materials and methods: The study was executed with radiochromic films. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…14 The Monaco VMC has been reported to achieve higher accuracy in near-surface doses. 17 Even though both VMC and AXB use Monte Carlo-based algorithms, the surface dose difference in the current study may be thus at least partly explained with differences between the algorithms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…14 The Monaco VMC has been reported to achieve higher accuracy in near-surface doses. 17 Even though both VMC and AXB use Monte Carlo-based algorithms, the surface dose difference in the current study may be thus at least partly explained with differences between the algorithms.…”
Section: Discussionmentioning
confidence: 77%
“…found 2.4 ± 2.1 mm maximum swelling in 93 patients, with 12 patients (13%) having swelling exceeding 8 mm. 17 Jain et al . reported nine of ten patients having deformations between 6 and 8 mm, and one patient had 10-mm deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results (Table 2) show that TPS seems to underestimate surface doses. There are many articles that use Monte Carlo to simulate the surface dose in breast cancer radiotherapy [47][48][49]. Arbor et al re ported a mean difference of 7% for Monte Carlo and 25% for the TPS compared with measurement data in the build-up range [50].…”
Section: Discussionmentioning
confidence: 99%
“…[12] Akino et al [13] compared the radiochromic film measurements with AAA calculations for different radiotherapy techniques including IMRT in breast cancer treatments and found that the calculation algorithm underestimated the doses near the surface by 15%-30%. They also reported that the et al [14] pointed out that an increase in dose uniformity might result in the reduction of surface dose. Another study explained that the dose distributed around the target causes lower doses at the surface.…”
Section: Open Field Irradiation a Comparison Between Film Measurementmentioning
confidence: 92%